Developing a biocontrol strategy to protect stored potato tubers from infestation with potato tuber moth species in the Andean region - Schaub, B.; Kroschel, Jürgen (Wiley, 2018)
Heavy infestations of stored potato (Solanum tuberosum L.) tubers by the two potato tuber moth species Symmetrischema tangolias (Gyen) and Tecia solanivora (Povolny) frequently occur in Andean potato‐growing regions of Ecuador. The aim of the study was to develop a biological control strategy for both species using powder formulations made of inert substances, Phthorimaea operculella (Zeller) granulovirus (PhopGV) and Bacillus thuringiensis Berliner subsp. kurstaki (Btk). The LC50 of PhopGV on T. solanivora was 0.33 LE/L, and Btk caused 82.7% mortality at a concentration of 100 g/L in bioassays. The efficacy of talcum, kaolin, calcium carbonate and sand ranged between 76.2% and 98.7%. Calcium carbonate was highly effective to control both species; however, its efficacy was affected by the relative humidity and dropped to 55.4% at relative humidity of 100%. PhopGV at concentrations of five larvae equivalents (LE) per kg kaolin and Btk at a concentration of 60 g Btk/kg talcum caused 95.7% and 88.1% mortality of T. solanivora, respectively. In storage experiments, the efficacy of calcium carbonate alone and in combination with PhopGV (20 LE/kg) and Btk (15 g/kg) caused 95.0–99.8% mortality of T. solanivora in all treatments and reduced infestation on potato tubers by 83.6%–91.0%. In the case of S. tangolias, Btk significantly increased mortality to 96.5% compared with calcium carbonate alone and reduced tuber infestation by 83.4%. Storage of potato tubers in thin layers enhanced the efficacy of the calcium carbonate treatment compared with storage in bags. It was concluded that calcium carbonate alone seems to be appropriate for the control of T. solanivora, and an addition of 15 g Btk/kg would improve the control of S. tangolias. It is suggested to test these new formulations under on‐farm storage conditions.